Combination Effect of Hemostatic and Disinfecting Agents on Micro-leakage of Restorations Bonded with Different Bonding Systems - Farhadpour H; Sharafeddin F; ,Akbarian S; Azarian B (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Hemostatic agents may affect the micro-leakage of different adhesive systems. Also, chlorhexidine has shown positive effects on micro-leakage. However, their interaction effect has not been reported yet. Objectives: To evaluate the effect of contamination with a hemostatic agent on micro- leakage of total- and self-etching adhesive systems and the effect of chlorhexidine application after the removal of the hemostatic agent. Materials and Methods: Standardized Class V cavity was prepared on each of the sixty caries free premolars at the cemento-enamel junction, with the occlusal margin located in enamel and the gingival margin in dentin. Then, the specimens were randomly divided into 6 groups (n = 10) according to hemostatic agent (H) contamination, chlorhexidine (CHX) application, and the type of adhesive systems (Adper Single Bond and Clearfil SE Bond) used. After filling the cavities with resin composite, the root apices were sealed with utility wax. Furthermore, all the surfaces, except for the restorations and 1mm from the margins, were covered with two layers of nail varnish. The teeth were immersed in a 0.5% basic fuschin dye for 24 hours, rinsed, blot-dried and sectioned longitudinally through the center of the restorations bucco- lingualy. The sections were examined using a stereomicroscope and the extension of dye penetration was analyzed according to a non-parametric scale from 0 to 3. Statistical analysis was performed using Kruskal-Wallis test and Mann-Whitney U-test. Results: While ASB group showed no micro-leakage in enamel, none of the groups showed complete elimination of micro-leakage from the dentin. Regarding micro- leakage at enamel, and dentin margins, there was no significant difference between groups 1 and 2, 1 and 3, and 2 and 3 (p > 0.05). A significantly lower micro-leakage at the enamel and dentin margins was observed in group 3, compared to group 6. No significant difference was observed between groups 4 and 5 in enamel (p = 0.35) and dentin (p = 0.34). Group 6 showed significantly higher micro-leakage, compared to group 4 and 5 (p < 0.05). Conclusions: Hemostatic agent contamination had no significant effect on micro- leakage of total- and self-etching adhesive systems. Application of chlorhexidine after the removal of hemostatic agent increased micro-leakage in self-etching adhesives but did not affect when total-etching was used.